DYNAMICS OF GROUP COMMUNICATION IN ARISAN'S ACTIVITIES - Ilene; Tang Natasha; Siti Meisyaroh (Jurnal Komunikasi dan Bisnis, 2021)
This study observed urban lifestyle phenomenon in Jakarta, namely arisan. Conducted in the outskirt of Jakarta, which is Kelapa Gading. This study, which aimed to observe the phenomenon of life style through arisan activities, attempted to observe ideas that underlies the motives of individuals when participating in arisan group and when consuming goods in their daily life. The study found that identity was important in arisan. It emerged as arisan activities were dominated by consumption. Competition among the members of arisan group occurred as a result. It showed who had higher identity and who had not. The role of the leader of the group was interesting as well. The leader was succesful to persuade the members to follow her orders for the sake of arisan activity. The power of the leader was not realized by other members. Strong bond of friendship between the leader and the members made them entering a system where one controlled others on what needs to be controlled.